Project Based Learning (PBL) in English Drama Course: The Process and Its Impact on Students’ Speaking Skill - Woro Kusmaryani (Muhammadiyah University of Mataram, 2022)
Project Based Learning (PBL) is a type of instruction whereby students spend a significant amount of time investigating and responding to a complex issue, problem, or challenge in order to learn knowledge and skills in the form of project. The objectives of this research were revealed the running process of PBL in English Drama course and investigated its impact on students’ speaking skill. This research was mixed-methods research, a case study at English Education Department of Universitas Borneo Tarakan. One lecturer and one class of students who attended the English Drama course served as the research subjects. This research collected quantitative and qualitative data such as documents, observation, and test. This data was analyzed quantitatively and qualitatively through coding and statistical analysis paired t-test. The results showed that the running process including Investigation, Planning, Implementation, and Reflection. The paired t-test result showed that Sig. 0.000 < 0.05, PBL implementation significantly enhances students' speaking abilities in English drama performance.